(131)I-labeled polyethylenimine-entrapped gold nanoparticles for targeted tumor SPECT/CT imaging and radionuclide therapy - Sun, Na (Int J Nanomedicine, 2019)
Purpose: Polyethylenimine (PEI) has been widely used as a versatile template to develop multifunctional nanosystems for disease diagnosis and treatment. In this study, we manufactured iodine-131 ((131)I)-labeled PEI-entrapped gold nanoparticles (Au PENPs) as a novel nanoprobe for single-photon emission computed tomography/computed tomography (SPECT/CT) imaging and radionuclide therapy. Materials and methods: PEI was PEGylated and sequentially conjugated with Buthus martensii Karsch chlorotoxin (BmK CT, a tumor-specific ligand which can selectively bind to MMP2), 3-(4′-hydroxyphenyl)propionic acid-OSu (HPAO), and fluorescein isothiocyanate to form the multifunctional PEI template for entrapment of Au NPs. Then, the PEI surface was radiolabeled with (131)I via HPAO to produce the novel nanoprobe (BmK CT-Au PENPs-(131)I). Results: The synthesized multifunctional Au PENPs before and after (131)I radiolabeling were well-characterized as follows: structure, X-ray attenuation coefficient, colloid stability, cytocompatibility, and radiochemical stability in vitro. Furthermore, BmK CT-Au PENPs-(131)I were suitable for targeted SPECT/CT imaging and radionuclide therapy of tumor cells in vitro and in a xenograft tumor model in vivo. Conclusion: The developed multifunctional Au PENPs are a promising theranostic platform for targeted imaging and treatment of different MMP2-overexpressing tumors.